A Pleistocene freshwater ichthyofaunal assemblage from central Argentina: What kind of fishes lived in the Pampean lagoons before the extinction of the megafauna? - Bogan, Sergio (2020)
This study contributes to the knowledge of continental fishes recovered from sedimentary successions corresponding to the Bonaerean Stage/Age (late mid-Pleistocene) in the locality of Centinela del Mar, General Alvarado County, Buenos Aires province, Argentina. At this site we describe fossil fishes from a palaeolagoon, including Corydoras sp., Pimelodella sp., Rhamdia sp., Oligosarcus sp., small undetermined characids, Jenynsia sp. and Odontesthes sp. The recovered ichthyofaunal assemblage comprises at least seven taxa of Paranaean lineage. The taxonomic composition of the palaeoichthyofauna is quite comparable to that presently found in Bonaerean Watercourses of the Atlantic Drainage ecoregion. This suggests that local ichthyofaunal communities have remained relatively stable since the late mid-Pleistocene.